Partisipasi Masyarakat dalam Implementasi Program Kampung Iklim (Proklim) di Desa Bulota Kecamatan Telaga Jaya Kabupaten Gorontalo - Adisty Pradita Syahputri Moo; Ellys Rachman; Agus Pariono (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to provide an overview of community participation in the implementation of the Climate Village Program (PROKLIM) in Bulota Village, Telaga Jaya District, Gorontalo Regency. Data analysis uses qualitative analysis of the Miles & Huberman model. The results of the study indicate that Government Socialization has not been carried out by the relevant Agency and Village regarding the program. Viewed from the Supervision aspect, the relevant Agency has not supervised the program. And Viewed from the Community Involvement aspect, it is still lacking. The things that are suggested are the need for the relevant Agency to conduct socialization so that the community is involved and understands what the climate village program (PROKLIM) is. The need for supervision by the relevant Agency is carried out continuously, so that the implementation of the program is more effective in its utilization. And the need for the community to be fully involved so that they can participate both through energy, thoughts and funds for the implementation of the Climate Village Program (PROKLIM) to run well.